Hydrogel bowls for cleaning oil spills on water. (15th November 2018) - Tran, Van Tron; Xu, Xiubin; Mredha, Md. Tariful Islam; Cui, Jiaxi; Vlassak, Joost J.; Jeon, Insu
Abstract: We demonstrate a hydrogel bowl capable of selectively and rapidly collecting spilled oil while floating on water. The bowl has macroscopic openings in its sidewall, and its surface is first coated with octadecyltrichlorosilane (OTS) and then with diffusion pump oil, which imparts exceptional hydrophobic, oleophilic, and high oil wettability properties. The use of a hydrogel makes it possible to obtain surface hydrophobicity and oleophilicity, while also being inexpensive, eco-friendly, and easy to fabricate. Using a prototype of the bowl and a small pump system, we demonstrate that oils with a broad range of viscosities (2.7–2000.0 cSt at 20–40 °C) are more rapidly and efficiently collected from the surface of both pure water and seawater than with any other reported technique. The hydrogel bowl can collect oil for more than one month without losing its efficiency and can be stored in oil for reuse. Therefore, such hydrogel bowls represent a new alternative to conventional oil spill remediation techniques. Graphical abstract: Image 1 Highlights: Low-cost hydrogel bowls were prepared for the selective removal of oil from water. Hydrophobic, oleophilic, and high oil wettability properties of the hydrogel bowl surface were achieved. Resultant moments around the macroscopic openings control water flow. Fast and efficient oil retrieval for a broad range of viscosities was achieved. Hydrogel bowls are durable and scalable without significant loss in performance.